GE_GERICHTE C/25296/2016 vom 23. März 2018 - GE Cour de justice (2018)
OBLIGATION D'ENTRETIEN ; TRAIN DE VIE ; DÉBUT ; BIENS DE L'ENFANT ; PROTECTION DE L'UNION CONJUGALE | CC.276; CC.285.al1; CC.285.al2